Primordial Cause of Armament, Disarmament, Weaponry and Weapons of Mass Destruction - Effiong Ekpo (International Studies Journal, 2022)
The entirety of humanity has been confronted with a serious threat to security, especially since after the cold war. To this fact, the concept of conflict and peace situate themselves in the heart of the contemporary man. This paper set to evaluate the level of primordial causes of armament, disarmament, weaponry and weapons of mass destruction. It used the change of attitude which led to the 1995/1996 review conference of the 1981 convention on prohibition or restrictions on the use of Certain Conventional Weapons (CCW) which may be deemed to be excessively injurious or to the indiscriminate effect as guide in the study. It traced the intractable problem to the emergence of civil wars of diverse intensity which have painted the world with red, which also facilitated the proliferation and spread of illicit small arms, weapons landmines and weapons of mass destruction. The paper postulates that deadly conventional weaponry and weapons of mass destruction are destructive weapons bearing a symmetrical non pictorial design should be discouraged. Also threats of war, whether explicit or implicit has always been an instrument of policy whereby one government dissuaded another from pursuing certain courses of action, be encouraged. This paper x[1]rayed the effect of proliferations of armament and weapons of mass destruction. The paper adopted conflict theory as analytical framework. The paper arrives at the conclusion that the causes of armament, disarmament, weaponry and weapon of mass destruction needs concerted effort of all both in Africa and internationally. The paper recommends that considering the anarchical nature of the international system, the world truly needed peace. Armed proliferation, it sources, ranging from technological advancement, offensive and defensive systems, economic boom, expansionist policy, growing disparity between the rich and the poor should back up with effective law creation enforcement and protection.